Shortcut Approach to 1,4-Diazepine from 3-Pyridylnitrene Intermedietes under Mild Condition - Ulfa, Siti Mariyah; Okamoto, Hideki; Satake, Kyosuke (Chemistry Department, The University of Brawijaya, 2014)
The reaction of nitropyridine derivatives and tributylphosphine (Bu3P) with the existence of nucleophilic solvent gives ring expansion product as diazepines in medium yield. Reaction mechanism subjected the formation of phenylnitrene, followed by intramolecular electrophilic insertion reaction to pyridine ring and subsequent ring enlargement. The intermediate in the reaction confirmed by computational calculation using B3LYP/6-31G* level. The intramolecular insertion reaction of pyridylnitrene is considered suppressed by the low HOMO (-9.932 eV) energy level of pyridine ring compared to that of benzene (-9.653 eV), hence 1,4-diazepine is obtained when employed 3-nitro-2,6-lutidine as starting material. The formation of diazepines was confirmed by the analysis of 1H NMR data. Separation of the product mixture using column chromatography on SiO2 was carried out and found to give expected diazepine along with the reduction product.